Diversidade morfológica e molecular em Piper (Piperaceae) em um fragmento de Floresta Atlântica - Christ, Jheniffer Abeldt (2016)
The conservation and management of the Atlantic Forest depends upon reliable knowledge about how many and which species this biome shelters. Floristic inventories have an important role in this process, especially when conducted in poorly known remnants, with a high conservation priority. This paper presents the study of the genus Piper (Piperaceae) in the Mata das Flores State Park, Castelo municipality, Espírito Santo State (ES). The study was based on the analysis of dried specimens, as well as those observed in the field, from February 2012 to August 2015. Twenty species of piper were identified. Amongst these species, Piper dilatatum, P. macedoi and P. piliovarium were recorded for the first time for the Espírito Santo State. Piper bicorne, an endemic species from ES and known only for the Santa Leopoldina municipality, had its geographical distribution expanded to the Castelo municipality. Most of the Piper species in the MFSP occur in valleys, and they are commonly found near watercourses. This is worrying given that these areas are just the most affected by the expansion of the rural and urban areas that surround the Park.